2001
DOI: 10.1111/j.1574-6968.2001.tb10752.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity among various oral Treponema species and cloning of a prtP-like gene of Treponema socranskii subsp. socranskii1

Abstract: The proteolytic activity of 11 treponemal strains representing different phylogenetic groups was investigated by SDS–polyacrylamide gel electrophoresis with copolymerised casein, gelatin and fibrinogen as substrates. The activity was specified to be trypsin‐ and chymotrypsin‐like by the cleavage of synthetic substrates BAPNA and SAAPFNA, respectively. Nine strains degrade casein and the synthetic substrate BAPNA. Chymotrypsin‐like activity specifically inhibited by phenylmethylsulfonyl fluoride was found in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Riviere et al (2002) detected several species of oral spirochaetes including T. socranskii in the brain cortex of patients with Alzheimer's disease by PCR and immunohistochemical analyses. A protease showing chymotrypsin-like activity was identified in this bacterium (Correia et al, 2003;Heuner et al, 2001). More recently we observed that T. socranskii induced osteoclastogenesis by upregulating prostaglandin E 2 , which stimulated the receptor activator of nuclear factor-kB ligand .…”
Section: Introductionmentioning
confidence: 72%
“…Riviere et al (2002) detected several species of oral spirochaetes including T. socranskii in the brain cortex of patients with Alzheimer's disease by PCR and immunohistochemical analyses. A protease showing chymotrypsin-like activity was identified in this bacterium (Correia et al, 2003;Heuner et al, 2001). More recently we observed that T. socranskii induced osteoclastogenesis by upregulating prostaglandin E 2 , which stimulated the receptor activator of nuclear factor-kB ligand .…”
Section: Introductionmentioning
confidence: 72%